THE MEANING OF LETTERS IN LITERATURE AND THEIR ROLE IN FICTION STORIES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Letter is a concise, compact and impressive presentation of human communication  and  an effective way of communicating feelings and confessions.